The Impact of Pollution on Worker Productivity - Zivin, Joshua Graff; Neidell, Matthew (American Economic Review, 2012)
This paper assesses the impact of pollution on worker productivity by relating exogenous daily variations in ozone with productivity of agricultural workers as recorded under piece rate contracts. We find robust evidence that ozone levels well below federal air quality standards have a significant impact on productivity. These results suggest that, in contrast to common characterizations of environmental protection as a tax on producers, environmental protection can also be viewed as an investment in human capital, and thus a tool for promoting economic growth.